Frauen in Aktion. Die Wahrnehmung von Frauen im bewaffneten Einsatz im Spanischen Bürgerkrieg in der internationalen Presse - Hansen, Christin (Patrix. Patriarchale Systematik und ihre Verdinglichung)

Experimental observation of topological quantum criticality - Barkhofen, Sonja; De, Syamsundar; Sperling, Jan; Silberhorn, Christine; Altland, Alexander; Bagrets, Dmitry; Kim, Kun Woo; Micklitz, Tobias (Physical Review Research)
We report on a photonic simulator of the critical state forming at the quantum phase transition between topologically distinct Anderson insulator phases. We observe a time-staggered profile in the circular photon polarization, which originates from the interplay of a chiral and sublattice symmetry, and has recently been suggested as a signature for topological Anderson criticality within the setup. We discuss the role of statistical detuning from criticality and show that the controlled breaking of phase coherence removes the signal, revealing its origin in quantum coherence. Published by the American Physical Society 2024

Evidenzbasierung. Eine wissenschaftskritische und fachsensible Perspektive - Scharlau, Ingrid; Jenert, Tobias (40 Begriffe für eine Schreibwissenschaft: Konzeptuelle Perspektiven auf Praxis und Praktiken des Schreibens)

Wo wir herkommen und wo es hingeht - Scharlau, Ingrid; Jenert, Tobias (Wissenschaftsdidaktik als kritische Kommunikationsanalyse. Ein Sammelband zur Weiterführung eines Gedankens von Ludwig Huber)

Textbook und Anti-Textbook: Zwei Lehrbücher in der Volkswirtschaftslehre - Jenert, Tobias (Wissenschaftsdidaktik als kritische Kommunikationsanalyse. Ein Sammelband zur Weiterführung eines Gedankens von Ludwig Huber)

Einleitung: Zur Wissenschaftsdidaktik - Scharlau, Ingrid; Jenert, Tobias (Wissenschaftsdidaktik als kritische Kommunikationsanalyse. Ein Sammelband zur Weiterführung eines Gedankens von Ludwig Huber)

Symmetry-protected TM modes in rib-like, plus-shaped optical waveguides with shallow etching - Üstün, Necati; Farheen, Henna; Hammer, Manfred; Förstner, Jens (Journal of the Optical Society of America B)
Lateral leakage of TM modes in dielectric optical waveguides of rib/ridge or strip-loaded types can be fully suppressed, if the waveguide core is formed not through a strip that protrudes at one side (up) from the remaining lateral guiding slab, but through parallel strips on both sides (up and down), such that the resulting cross section becomes vertically symmetric. The fairly general arguments underlying the leakage suppression apply to TM modes of all orders simultaneously, and are independent of wavelength. These plus-shaped waveguides support strictly guided, non-leaky TM modes for, in principle, arbitrarily shallow etching.
Keywords: tet_topic_waveguide

Eine inklusive Lehr-Lernumgebung für die Leitidee „Daten und Zufall“ in der Primarstufe - Biehler, Rolf; Frischemeier, Daniel (Inklusives Lehren und Lernen von Mathematik)

Richard Saage, Eva-Maria Seng, Gebaute Utopien. Zwischen frühneuzeitlicher Idealstadt und den Architektur- und Stadtplanungen der russischen Avantgarde der 1920er Jahre - Seng, Eva- Maria; Saage, Richard (Stadtträume – Traumstädte. Tagungsband der 50. Jahrestagung des Südwestdeutschen Arbeitskreises für Stadtgeschichtsforschung)

Wackelbrücke oder WLAN? Bedürfnisse von Erwachsenen auf Kinderspielplätzen - Kukuk, Marc; Meier, Heiko; Niemand, Marcus (Playground@Landscape)

Predictors of primary school teachers’ self-efficacy beliefs for inclusive education - Franzen, Katja; Moschner, Barbara; Hellmich, Frank (Frontiers in Education)

Ideal- und Planstädte im deutschen Südwesten in der Frühen Neuzeit - Seng, Eva- Maria (Stadtträume – Traumstädte. Tagungsband der 50. Jahrestagung des Südwestdeutschen Arbeitskreises für Stadtgeschichtsforschung)

Wie Schüler Fälle bearbeiten. Explorative Einblicke in Fallarbeit im Schulfach Erziehungswissenschaft - Gather, Katharina; Engemann, Mario; Hoppe, Laura; Martin, Alexander (Pädagogische Rundschau)

Stone or timber: The development of the concept of authenticity regarding entries into the World Heritage List - Seng, Eva- Maria (Research of Chinese Art history and Theory)

Daten-Spürnasen auf Spurensuche: Datenanalyse in der Grundschule mit digitalen Werkzeugen - Biehler, Rolf; Frischemeier, Daniel

Platform Competition and Price Coercion - Vijairaghavan, Vaarun; Hidaji, Hooman; Kundisch, Dennis; Zimmermann, Steffen (Proceedings of the Conference on Information Systems and Technology (CIST))

Numerical surgery for mean curvature flow of surfaces - Kovács, Balázs (SIAM Journal on Scientific Computing)

Der Fall Geldbach. Ein Detektivspiel als Grundlage für die Behandlung verschiedener Nebensatzstrukturen - Menke, Peter (Praxis Deutsch)

NetNN: Neural Intrusion Detection System in Programmable Networks (Second Best Paper Award) - Razavi, Kamran; Davari Fard, Shayan; Karlos, George; Nigade, Vinod; Mühlhäuser, Max; Wang, Lin (Proceedings of the IEEE International Symposium on Computers and Communications (ISCC))

Selective Encoding: Reducing the Burden of Transcription for Digital Musicologists - Saccomano, Mark; Rosendahl, Lisa; Lewis, David; Hankinson, Andrew; Kepper, Johannes; Page, Kevin; Shibata, Elisabete (Journal of the Text Encoding Initiative)
Keywords: DigitaleEdition